The Effect Of Consuming Seaweed On Hemoglobin Levels Of Pregnant Women - Nurasmi; Gusriani; Wahida; Nur Indah Noviyanti (International Journal of Health and Pharmaceutical (IJHP), 2022)
Anemia of pregnancy is a condition of pregnant women with hemoglobin levels less than 11gr/dl in the first and third trimesters and less than 10.5gr/dl in the second trimester. Hemoglobin (Hb) is a red pigmented protein found in red blood cells. Increasing Hb can be done by using Seaweed, because seaweed contains iron, minerals, B complex vitamins, protein and others. The purpose of this study was to analyze the effectiveness of seaweed consumption on increasing Hb levels in pregnant women. This research is a Quasy Experiment research with one group pretest-posttest design. Respondents were 10 pregnant women with anemia in Tarakan City, where samples were taken by purposive sampling. The Hb of pregnant women before being given seaweed was the majority 9.21 g/dl, the lowest Hb was 7 g/dl and the highest was 9.8 g/dl. The Hb of pregnant women after being given seaweed was the majority 10 g/dl, the highest Hb was 12.7 g/dl and the lowest was 7 g/dl. The results showed p value <0.0001 (p<0.05) with a change in the mean before being given the intervention from 8.94 g/dl to 10.93 g/dl after being given the intervention. Thus, seaweed is very effective in increasing Hb levels in anemic pregnant women. Anemia of pregnancy is a condition of pregnant women with hemoglobin levels less than 11gr/dl in the first and third trimesters and less than 10.5gr/dl in the second trimester. Hemoglobin (Hb) is a red pigmented protein found in red blood cells. Increasing Hb can be done by using Seaweed, because seaweed contains iron, minerals, B complex vitamins, protein and others. The purpose of this study was to analyze the effectiveness of seaweed consumption on increasing Hb levels in pregnant women. This research is a Quasy Experiment research with one group pretest-posttest design. Respondents were 10 pregnant women with anemia in Tarakan City, where samples were taken by purposive sampling. The Hb of pregnant women before being given seaweed was the majority 9.21 g/dl, the lowest Hb was 7 g/dl and the highest was 9.8 g/dl. The Hb of pregnant women after being given seaweed was the majority 10 g/dl, the highest Hb was 12.7 g/dl and the lowest was 7 g/dl. The results showed p value <0.0001 (p<0.05) with a change in the mean before being given the intervention from 8.94 g/dl to 10.93 g/dl after being given the intervention. Thus, seaweed is very effective in increasing Hb levels in anemic pregnant women.